Research on teacher stress : implications for the COVID-19 pandemic and beyond - McCarthy, Christopher J.; Lambert, Richard G. (Research on stress and coping in education series., 2023)
"This volume informs our understanding of how educational settings can respond to the challenges of the COVID-19 pandemic and beyond. Teaching has always been a challenging profession but the pandemic has added unprecedented levels of demands. Much of what we know about stress and trauma in education predates the COVID-19 pandemic. As the pandemic recedes, it seems likely that recruiting and retaining teachers, always a challenge, will become even more difficult. This could not be worse for students, who face steep losses in their academic and socio-emotional progress after more than two years of pandemic-impacted schooling. The silver lining is that scholars who study the occupational health have spent the past several years studying the effect of the pandemic on teachers, which led us to edit this volume to collected what is known and have these experts explain how we can better support teachers in the future. This book documents the many impacts of the pandemic on the teaching profession, but also leverages research to chart a path forward. Part I examines the contours of stress, with a particular emphasis on COVID-19 impacts. These contributions range from parents' achievement worries to compassion fatigue, and, more optimistically, how teachers cope. Part II examines pandemic impacts on pre-school teachers, in both the U.S. and in Australia. Given the social distancing in place during the pandemic, pre-school students and their teachers were under unique demands, as there is no substitute for the personal connection critical at that age. It is likely that students entering elementary school in the next few years will have work to do in their social skills. Part III focuses on mentoring and stress during the pandemic. Mentoring is an important part of teacher's professional development, but the pandemic scrambled traditional forms of mentoring as all teachers were thrown into unfamiliar online technology. The final section of this book, Part IV, includes links between teacher stress and trauma during the pandemic. Clearly, with the ongoing nature of the pandemic, it is easy to see how trauma is likely to manifest in years to come. Readers of this book will better understand teacher demands, as well as the resources teachers will need going forward. Teachers made heroic efforts during the pandemic to help their students both academically and personally. We owe to them to learn from research during the pandemic that points to the way to a healthier occupational future"--